Antiretroviral drug concentrations in brain tissue of adult decedents. (1st November 2020) - Ferrara, Micol; Bumpus, Namandjé N.; Ma, Qing; Ellis, Ronald J.; Soontornniyomkij, Virawudh; Fields, Jerel A.; Bharti, Ajay; Achim, Cristian L.; Moore, David J.; Letendre, Scott L.
Abstract : Objective: Determine concentrations of antiretroviral therapy (ART) drugs in the human brain. Design: Cohort study of persons with HIV who consented to antemortem assessment and postmortem autopsy. Methods: Eleven persons with HIV who were taking ART at the time of death and had detectable concentrations of at least one ART drug in intracardiac aspirate at autopsy were evaluated. Autopsies were performed within 24 h of death and brain tissue was stored at −80 °C. Concentrations of 11 ART drugs were measured in three brain regions (globus pallidus, cortical gray matter, white matter) by HPLC tandem mass spectrometry with a lower limit of quantification of 25 ng/ml. Results: Participants were mostly men (82%) with a mean age of 40.4 years. Drug concentrations in brain tissue were highly variable and exceeded published concentrations in cerebrospinal fluid for several drugs, including for tenofovir, efavirenz, and lopinavir. Drug concentrations correlated most strongly between cortical gray matter and globus pallidus (rho = 0.70) but less well between globus pallidus and white matter (rho = 0.43). Combining all drugs and brain regions ( n  = 89), higher drug concentrations in brain were associated with longer estimated duration of HIV infection ( P  = 0.015), lower HIV RNA in plasma ( P  = 0.0001), lower nadir CD4 + T-cell count ( P  = 0.053), and worse neurocognitive performance ( P  = 0.017). Conclusion: This is the first analysis of ART drug concentrations in human brain tissue. Concentrations of several drugs in this analysis were similar to published concentrations in cerebrospinal fluid but others exceeded published concentrations. The association between higher drug concentrations in the brain and worse neurocognitive performance may indicate ART neurotoxicity.